1978
DOI: 10.1017/s0022112078002293
|View full text |Cite
|
Sign up to set email alerts
|

Structural similarity in radial correlations and spectra of longitudinal velocity fluctuations in pipe flow

Abstract: The paper describes correlation measurements in both broad and narrow frequency bands of the longitudinal velocity fluctuations in fully developed pipe flow at four positions for a reference probe whilst a second probe was traversed radially from deep in the sublayer to a position near the axis with both longitudinal and transverse separations zero (Δx = Δz = 0). Such measurements require that both the Covariant (Co) and Quadrature (Quad) correlations be determined for each of the 15 frequencies used to constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
38
0
4

Year Published

1988
1988
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 17 publications
14
38
0
4
Order By: Relevance
“…All the modes in the upper-right-hand corner of the spectral plane, which corresponds to the spectral production tail, have correlation heights which are larger than y + = 30, and are therefore essentially coherent over the full integration height. That result is consistent with those of Bullock, Cooper & Abernathy (1978), who computed covariances for velocity signals filtered in different frequency bands. In a pipe at Re τ = 2600 they found that the correlation coefficient of u between y + = 50 and all the y < y was larger than 0.6 when λ + x & 1000, but that it vanished in the sublayer for the shorter wavelengths λ + x < 250.…”
Section: Resultssupporting
confidence: 91%
“…All the modes in the upper-right-hand corner of the spectral plane, which corresponds to the spectral production tail, have correlation heights which are larger than y + = 30, and are therefore essentially coherent over the full integration height. That result is consistent with those of Bullock, Cooper & Abernathy (1978), who computed covariances for velocity signals filtered in different frequency bands. In a pipe at Re τ = 2600 they found that the correlation coefficient of u between y + = 50 and all the y < y was larger than 0.6 when λ + x & 1000, but that it vanished in the sublayer for the shorter wavelengths λ + x < 250.…”
Section: Resultssupporting
confidence: 91%
“…The double peak in iu(w) near the wall is also reported by others; fcr example, the double peak is in the data of Perry and Abell (1975) and in the data of Bullock et al (1978). Bullock et al (1978) At high enough Reynolds numbers, the separation between the low and high wavenumber regions will he large and the high wavenumber region will be isotý'opic and independent of the character of the production process which can be highly anisotropic.…”
Section: Perry and Abellsupporting
confidence: 74%
“…However, very near the wall'in the buffer region, whore the mean velocity gradient is large, the spectrum in the inertial wavenumber range reflects the influence of the production process, namely the mean velocity gradient (dU/dy), and that the spectrum in this range scales as Sk-1 . It is interesting to noto that Bullock et al (1978) also obtained a k-1 dependence to their near wall data (200<y+<500) which they attributed as being due to the predominance of the lower frequency peak (u wave) that was present in the spectral data. Nevertheless, the frequency of the velocity spectra can be used to gain insight to the turbulence structure of the flow field.…”
Section: Perry and Abellmentioning
confidence: 90%
See 2 more Smart Citations